Complicated Pneumococcal Meningitis in a Fully Vaccinated Child: Value of Magnetic Resonance Imaging Monitoring - Ilia, S.; Spanaki, A.-M.; Raissaki, M.; Spoulou, V. I.; Fitrolaki, M.-D.; Kanariou, M.; Tzanakaki, G.; Briassoulis, G. (Neuropediatrics, 2011)
We present a unique case of life-threatening pneumococcal meningitis complicated by vasculitis in a fully vaccinated 4-year-old female with the heptavalent conjugate vaccine for Streptococcus pneumoniae (PCV7). Serotype 23F was isolated in both blood and cerebral spinal fluid (CSF) samples. Pulses of methylprednisolone were promptly initiated in addition to antibiotics leading to a good recovery. CSF studies and magnetic resonance imaging (MRI) of the brain were used for diagnosis and monitoring the response to corticoid therapy. We report the investigations of a child with failure of PCV7 vaccine to protect against vaccine-serotype invasive disease. Use of corticosteroids and temporal association with changes in brain imaging are described for the first time in literature.
Keywords: meningitis; magnetic resonance imaging; pulse of steroids; vasculitis; Streptococcus pneumonia; PCV7